Effects of psychological interventions on anxiety in athletes: a meta-analysis based on controlled trials - Li, Houchen; Yang, Qingqiong; Wang, Bin (Frontiers in Psychology, 2025)
ObjectivesAnxiety is a prevalent psychological challenge in elite sports and complex training environments. This meta-analysis systematically evaluated the effects of psychological interventions on athletes’ anxiety levels.MethodsA systematic review and meta-analysis were conducted in accordance with PRISMA guidelines. PubMed, Web of Science, Scopus, and PsycINFO were searched from inception to December 5, 2024. Eligible studies were randomized controlled or quasi-experimental trials examining the effects of psychological interventions on anxiety in athletes. Standardized mean differences (SMD) with 95% confidence intervals were calculated using a random-effects model. Heterogeneity was assessed using the I2 statistic, and subgroup analyses were performed based on age, sport type, intervention method, and outcome measures.ResultsTwenty-four studies comprising 853 athletes were included. Psychological interventions significantly reduced athletes’ state anxiety (SMD = −0.99, 95% confidence interval [CI] − 1.16 to −0.81), representing a large effect. Subgroup analyses showed a large effect for adolescent athletes (SMD = −1.04, 95% CI − 1.53 to −0.56) and for athletes in individual sports (SMD = −1.12, 95% CI − 1.41 to −0.83), both exceeding the threshold for large effects. Among intervention types, traditional psychological skills training (PST) was more effective (SMD = −1.21, 95% CI − 2.11 to −0.31) than cognitive-behavioral therapy (CBT) or mindfulness training, also indicating a large effect but with a wide CI requiring cautious interpretation. Moreover, the choice of anxiety scale influenced effect estimates; the Competitive State Anxiety Inventory-2 (CSAI-2) yielded larger effect sizes than other instruments, highlighting its greater sensitivity to detecting changes in athletes’ anxiety levels.ConclusionPsychological interventions, particularly traditional psychological skills training (PST), meaningfully reduce anxiety in athletes, yet considerable heterogeneity and limited exploration of moderators remain. Future research should investigate how intervention effects differ across sport disciplines, gender, and competitive level, and should refine intervention components to identify the most efficient protocols.